Identification of genomic islands in Chilean Piscirickettsia salmonis strains and analysis of gene expression involved in virulence. Issue 10 (2nd February 2017) - Lagos, F; Cartes, C; Vera, T; Haussmann, D; Figueroa, J
Abstract: Piscirickettsia salmonis, an agent of Piscirickettsiosis, is the cause of major losses in the Chilean salmon industry. We identified, characterized and bioinformatically analysed genomic islands in field strains of P. Salmonis, using the bioinformatic software PIPS, that uses the characteristics of the islands of pathogenicity to identify them. We analysed nine partially sequenced genomes in different new field strains, and compared them with the LF‐89 (Type strain) genome, selecting a genomic island present in all of them. We then evaluated the relative expression of three genes present in that island. From the obtained results, we conclude that the expression of the tcf gene is directly proportional to the cytopathogenicity in vitro of the bacteria; the product of the dnsa gene could contribute to its pathogenicity, but would be potentiated by one or more factors. The product of the gene liso is necessary for the virulence process and could have functions in early stages of infection. Regarding the strains, the IBM‐040 strain showed a significant increase in the expression of all the genes in the study. Contrarily, LF‐89 only presented a significant increase in expression of the gene liso, which correlates with the cytopathogenicity in vitro observed in the SHK‐1 cells.